MANAJEMEN PEMBELAJARAN MATEMATIKA DALAM MENGIMPLEMENTASIKAN PENDIDIKAN KARAKTER - Eka Agustina (UNIVERSITAS BENGKULU, 2016)
The purpose of this study was to implement a character education in mathematics. The subjects of research are mathematics teachers and students in grade 2. This study is a qualitativeresearch. Data collected by observation, interview and documentation. The results of this study indicate that learning mathematics is already implementing a character education in Vocational High School Number 5 Bengkulu City.Keywords: mathematics learning, character education